Simulation and evaluation of circular and rectangular microstrip patch antenna / Shazwani Mohd. Ismail - Mohd. Ismail, Shazwani
This paper discovers the performance evaluation of circular and rectangular patch microstrip antennas. The study concentrates on frequency of 2.4GHz. in reference to the Nokia mobile phone characteristics. The antennas has been designed using three different materials; Perfect Electric Conductor (PEC) for ground plane, Flame Retardant 4 (FR-4) and Taconic RF-30 used as substrate and Copper for the patch. It has been simulated using Computer Simulation Technology (CST) Microwave Studio in CST2009 software. Return loss, input impedance, VSWR and farfield values obtained from simulations of both antennas were compared. The best performance for return loss, impedance Zll, VSWR and farfield out of both antennas was obtained through simulations. Circular patch antenna gave better results in comparison to rectangular patch antenna. The development of circular patch antenna is increasing and the future prospect of this antenna could expand rapidly with the adjustments of the sizes of patch and substrate permittivity selected.